General and Eating Disorder Specific Flexibility: Development and Validation of the Eating Disorder Flexibility Index (EDFLIX) Questionnaire - Dahlgren, Camilla Lindvall; Hage, Trine Wiig; Wonderlich, Joseph Arthur; Stedal, Kristin (Frontiers in Psychology, 2019)
Studies investigating cognitive flexibility in eating disorders are inconsistent, and although neuropsychological tests are commonly used to measure these skills, they may not be particularly effective in predicting every-day functioning. Also, extant studies have largely focused on flexibility in anorexia nervosa, with assessments targeting general rather than specific flexibility. Knowledge regarding eating disorder specific flexibility and flexibility in bulimia nervosa and binge eating disorder is still scarce. The aim of this study was to develop and validate a novel measure assessing general and eating disorder specific flexibility in a diagnostically diverse sample, and in healthy controls. A sample of 207 adult individuals with eating disorders (55% anorexia nervosa, 29% bulimia nervosa, 16% binge eating disorder) and 288 healthy controls responded to an online, 51-item, pilot questionnaire on eating disorder specific and general flexibility. An exploratory factor analysis in the clinical sample yielded a 36-item, three-factor solution capturing general flexibility, flexibility related to food and exercise, and flexibility concerning body shape and weight. Results showed that the measure had good to excellent internal consistency, and good convergent validity. A confirmatory factor analysis using data from healthy controls revealed good fit indexes, supporting the original factor solution. A receiver operating characteristics analysis demonstrated excellent accuracy in distinguishing scores from those with and without eating disorders. A cutoff score of 136 yielded the most balanced sensitivity and specificity. Significant differences in general and eating disorder specific flexibility were found between individuals with and without eating disorders. Overall, healthy controls achieved the highest flexibility scores, followed by those with binge eating disorders, bulimia nervosa, and anorexia nervosa. In sum this novel measure, the Eating Disorder Flexibility Index (EDFLIX) questionnaire, was found to be reliable and valid in the assessment of flexibility, with results offering support for the conceptual distinction between general and eating disorder related flexibility. Our results further provide strong evidence for the discriminant validity of the EDFLIX, indicating the utility of the assessment instrument for classification purposes.